Using TikTok to Boost Students’ Speaking Skills: Menggunakan TikTok untuk Meningkatkan Keterampilan Berbicara Siswa - Ningroom, Satya Churniati; Mandarani, Vidya (Indonesian Journal of Education Methods Development, 2024)
General Background: Speaking skills are essential for effective communication, particularly in the context of learning foreign languages such as English. Specific Background: Despite the importance of English proficiency for academic and global opportunities, many junior high school students struggle to master the language. Recent trends in social media, particularly TikTok, have emerged as potential tools for enhancing language learning engagement among youth. Knowledge Gap: While there is a growing body of research on the use of technology in education, limited studies have specifically focused on the application of TikTok to improve speaking skills in a structured learning environment. Aims: This study investigates the effectiveness of TikTok as a tool for improving English speaking skills among seventh-grade students in a junior high school. Results: Utilizing a pre-experimental case study design with 30 students, the study measured fluency, pronunciation, grammar, and comprehension through pre-tests and post-tests. The findings indicated a significant increase in average speaking scores from 58.67 to 68.67, demonstrating improvement after the TikTok-based intervention. Novelty: This research offers new insights into the innovative use of social media for language education. Implications: The results suggest that incorporating platforms like TikTok into English language instruction can create a more engaging and effective learning environment, fostering greater student interest and participation in language learning. Highlights: Improvement in Scores: Students' average speaking scores increased from 58.67 (pre-test) to 68.67 (post-test) after using TikTok. Engaging Learning Tool: TikTok is recognized as a contemporary and engaging platform for enhancing English speaking skills. Innovative Instruction: The study highlights the potential of using social media to diversify and enrich the English learning experience. Keywords: TikTok, English speaking skills, junior high school, innovative learning, language education.